Synchronous reference frame single-phase phase-locked loop (PLL) algorithm based on half-cycle DFT - Xia, Tao; Zhang, Xu; Tan, Guojun; Liu, Yezhao (IET power electronics, 2020)
In single-phase power and energy applications, sliding discrete Fourier transform (SDFT) filter based quadrature signal generation is a well-known tool for designing advanced phase-locked loops (PLLs), particularly for applications where high disturbance rejection ability is demanded. The SDFT-based PLL, nevertheless, has a limited ability in achieving fast response (a response time more than one cycle of the nominal frequency). To deal with this problem, a synchronous reference frame PLL based on half-cycle DFT (HCDFT) is proposed, enabling a fast and accurate synchronisation even in distorted grid. In this study, the fundamental voltage of the PLL input signal is obtained by a HCDFT filter. Then, phase, frequency and amplitude can be detected by the improved synchronous reference frame phase-locked loop (SRF-PLL). Besides, in order to solve the phase error when the frequency changes, a phase compensator is used. The HCDFT-based SRF-PLL method proposed in this study is compared, through experimental results, with a number of conventional methods, showing that the phase can be estimated under grid voltage disturbances accurately and quickly, which verifies the effectiveness and superiority of the proposed algorithm.